Y-chromosome phylogeny in the evolutionary net of chamois (genus Rupicapra) - Pérez, Trinidad (BioMed Central, 2011)
BACKGROUND: The chamois, distributed over most of the medium to high altitude mountain ranges of southern Eurasia, provides an excellent model for exploring the effects of historical and evolutionary events on diversification. Populations have been grouped into two species, Rupicapra pyrenaica from southwestern Europe and R. rupicapra from eastern Europe. The study of matrilineal mitochondrial DNA (mtDNA) and biparentally inherited microsatellites showed that the two species are paraphyletic and indicated alternate events of population contraction and dispersal-hybridization in the diversification of chamois. Here we investigate the pattern of variation of the Y-chromosome to obtain information on the patrilineal phylogenetic position of the genus Rupicapra and on the male-specific dispersal of chamois across Europe. RESULTS: We analyzed the Y-chromosome of 87 males covering the distribution range of the Rupicapra genus. We sequenced a fragment of the SRY gene promoter and characterized the male specific microsatellites UMN2303 and SRYM18. The SRY promoter sequences of two samples of Barbary sheep (Ammotragus lervia) were also determined and compared with the sequences of Bovidae available in the GenBank. Phylogenetic analysis of the alignment showed the clustering of Rupicapra with Capra and the Ammotragus sequence obtained in this study, different from the previously reported sequence of Ammotragus which groups with Ovis. Within Rupicapra, the combined data define 10 Y-chromosome haplotypes forming two haplogroups, which concur with taxonomic classification, instead of the three clades formed for mtDNA and nuclear microsatellites. The variation shows a west-to-east geographical cline of ancestral to derived alleles. CONCLUSIONS: The phylogeny of the SRY-promoter shows an association between Rupicapra and Capra. The position of Ammotragus needs a reinvestigation. The study of ancestral and derived characters in the Y-chromosome suggests that, contrary to the presumed Asian origin, the paternal lineage of chamois originated in the Mediterranean, most probably in the Iberian Peninsula, and dispersed eastwards through serial funding events during the glacial-interglacial cycles of the Quaternary. The diversity of Y-chromosomes in chamois is very low. The differences in patterns of variation among Y-chromosome, mtDNA and biparental microsatellites reflect the evolutionary characteristics of the different markers as well as the effects of sex-biased dispersal and species phylogeography.